1978
DOI: 10.1111/j.1469-8986.1978.tb01417.x
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Attention Across Auditory Input Channels: An Assessment Using the Human Evoked Potential

Abstract: In order to determine the extent to which distraction disrupts performance when attention is divided, the distribution of attention across five auditory input channels was assessed using the N1 component of the human auditory evoked potential. In addition, the possibility that methylphenidate (Ritalin) affects the distribution of attention across input channels was tested. Sixteen subjects performed a tone discrimination task under conditions of focused attention and divided attention, both with and without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 20 publications
2
18
1
1
Order By: Relevance
“…A narrow focus of attention indexed by Nl/Nd was also reported by Schwent, Snyder, and Hillyard (1976) in a three-channel design. However, in a similar type of study that presented tones over five channels distinguished by location and pitch, Hink et al (1978) found that NIlNd amplitudes were enhanced not only by the attended-channel tones but also by the tones in adjacent channels. Possible factors that might account for these differing patterns of results among studies include differences in stimulus presentation rate, spatial separation between auditory channels, frequency separation between channels, and type of attention-directing task.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…A narrow focus of attention indexed by Nl/Nd was also reported by Schwent, Snyder, and Hillyard (1976) in a three-channel design. However, in a similar type of study that presented tones over five channels distinguished by location and pitch, Hink et al (1978) found that NIlNd amplitudes were enhanced not only by the attended-channel tones but also by the tones in adjacent channels. Possible factors that might account for these differing patterns of results among studies include differences in stimulus presentation rate, spatial separation between auditory channels, frequency separation between channels, and type of attention-directing task.…”
mentioning
confidence: 86%
“…The identification of such targets is associated with a longer latency positive ERP component (the "P3" or "P300") wave having a peak latency of 300-400 msec. A number of studies have shown that the P3 is specifically elicited by targets in the attended channel and not by comparable deviant stimuli in an unattended channel (e.g., Hillyard et al, 1973;Hink, Fenton, Pfefferbaum, Tinklenberg, & Kopell, 1978). These findings have suggested that the NIlNd and P3 waves are indices of two hierarchically organized levels of selection, with the NIlNd reflecting an initial between-channel selection based on easily discriminable cues and the P3 indexing a subsequent withinchannel target selection following a more elaborated and detailed processing of the relevant stimulus properties.…”
mentioning
confidence: 99%
“…The attention-related changes in ERPs occur when participants attend to a particular stream of sounds in the presence of one or more different streams of distracting stimuli and when stimulus sequences are easily discriminated, whether they are distinguished by spatial position, frequency, or both spatial position and frequency (58)(59)(60). Although there is one report of the habituation of the Nde (61), performance and Nde amplitude are usually maintained over long sessions (59,62,63). The Nde amplitudes and latencies are also little affected by repeated testing (34, 64).…”
Section: Electrophysiological Studies Of Auditory Selective Attentionmentioning
confidence: 99%
“…When the task-relevant and task-irrelevant tones are highly distinctive and presented at short ISIs (e.g., 200-400 msec), the selective attention effects on ERPs can occur at latencies as short as 30 msec following stimulus onset (56,57). The attention-related changes in ERPs occur when participants attend to a particular stream of sounds in the presence of one or more different streams of distracting stimuli and when stimulus sequences are easily discriminated, whether they are distinguished by spatial position, frequency, or both spatial position and frequency (58)(59)(60). Although there is one report of the habituation of the Nde (61), performance and Nde amplitude are usually maintained over long sessions (59,62,63).…”
Section: Electrophysiological Studies Of Auditory Selective Attentionmentioning
confidence: 99%
“…It is well documented that methlphenidate (MPH) improves vigilance (Coons et al, 1981;Strauss et al, 1984;Peloquin & Klorman, 1986;Camp-Bruno & Herting, 1994;Hermens et al, 2007) and divided/focused attention (Hink et al, 1978) in normal humans and attentional performance in rats (Bizarro et al, 2004). Methylphenidate is also particularly effective at ameliorating the attentional difficulties in children and adults with Attention Deficit Hyperactivity Disorder (ADHD; Brown et al, 2005;Tucha et al, 2006).…”
Section: Introductionmentioning
confidence: 99%